TOPOLOGICAL OPTIMIZATION DESIGN OF TB LEVEL ENERGY ABSORBER BOX OF GUIDING CRASH CUSHION - LEI ZhengBao; LIU MeiGang; ZHANG JiaBo; CHEN XiaoYong (Jixie qiangdu)
In order to reduce the weight of the steerable crash cushion,based on the collision resistance topology optimization method of hybrid cellular automata,the multi-condition topology optimization analysis of the energy absorption box of the steerable crash cushion was carried out,and the topology configuration of the energy absorption box was extracted. Moreover,the cross-sectional parameters of the rectangular cross-section energy absorption box are optimized by using orthogonal test design method and taking the maximum acceleration in the multi-condition collision of the vehicle as an evaluation index,and the optimal parameter combination of the rectangular cross-section energy absorption box is determined. Finally,the multi-condition finite element simulation analysis of the crash cushion before and after orthogonal test optimization is carried out,and the acceleration of the optimized crash cushion under forward collision condition is compared with that of the existing crash cushion.The results show that the energy absorption box obtained through optimization has better buffering performance than that before optimization,and can better protect the safety of passengers.